Impact of functional training on cardiac autonomic modulation, cardiopulmonary parameters and quality of life in healthy women - Barbosa, Marianne Penachini da Costa de Rezende [UNESP]; Netto Júnior, Jayme [UNESP]; Cassemiro, Bruna Montechieze [UNESP]; Souza, Naiara Maria de [UNESP]; Bernardo, Aline Fernanda Barbosa [UNESP]; Silva, Anne Kastelianne França da [UNESP]; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Wiley-Blackwell, 2015)
Functional training (FT) promotes benefits in various physical abilities; however, its effect on autonomic modulation, cardiorespiratory parameters and quality of life in the healthy adult population is unknown, and thus, the aim of this study was to evaluate the influence of  FT on these variables in healthy young women. The study consisted of 29 women, distributed into two groups: the FT Group (FTG; n = 13; 23 ± 2·51 years; 21·90 ± 2·82 kg m(-) ²) and the Control Group (CG; n = 16; 20·56 ± 1·03 years; 22·12 ± 3·86 kg m(-) ²). The FTG performed periodized FT for 12 weeks, three times a week. The following were evaluated: autonomic modulation (heart rate variability), cardiorespiratory parameters and quality of life (SF-36 Questionnaire). The Student's t-test for unpaired data or the Mann-Whitney test was used to compare the differences obtained between the final moment and the initial moment of the studied groups (P<0·05). The FTG demonstrated significant improvements in quality of life and autonomic modulation (P<0·05), but not in the cardiorespiratory parameters. Functional training was able to produce improvements in autonomic modulation and quality of life.
Keywords: Autonomic nervous system; Exercise and young adult; Heart rate; Parasympathetic nervous system; Resistance training